EFFECTIVENESS OF ALLEN BUERGER EXERCISE IN PREVENTING PERIPHERAL ARTERIAL DISEASE AMONG PEOPLE WITH TYPE II DIABETES MELLITUS - DR.S.ARUNA; MRS.THENMOZHI.P (International Journal of Pharma and Bio Sciences, 2015)
Diabetes mellitus increases the risk of lower extremity peripheral arterial disease by 2 to 4 times and is present in 12% to 20% of persons with lower extremity peripheral arterial disease. The risk of developing lower extremity peripheral arterial disease is proportional to the severity and duration of diabetes and 7- to 15-fold more likely to undergo a major amputation is also greater in diabetics than non diabetics. To determine the effectiveness of Allen Buerger Exercises among people with Type II Diabetes Mellitus by using Ankle –Brachial Index. Experimental Research Design with 30 samples in experimental group and 30 samples in control group were selected by using random sampling technique at Kuthambakkam village. Peripheral arterial disease and the effectiveness of Allen Buerger exercise was assessed by Ankle Brachial index Scale. The findings of the study revealed that there is a significant improvement in Ankle-Brachial index Score in preventing peripheral arterial disease among people with Diabetes Mellitus in experimental group after receiving Allen Buerger exercise at the level of P<0.05 and there is s significant association between the duration of diabetes mellitus and the pretest score of ABI. Study participants got benefited by Allen Buerger exercise in preventing Peripheral Arterial Disease.